2021
DOI: 10.1149/1945-7111/ac069b
|View full text |Cite|
|
Sign up to set email alerts
|

Good Structural Stability of Si Anodes Achieved through Dispersant Addition and Use of Carbon Fabric as Conductive Framework

Abstract: Carbon fabric is proposed as the electrode support instead of Cu foil as the current collector in the fabrication of Si-anode, in order to prevent electrode pulverization during cell charge/discharge. Polyvinylpyrrolidone is used as a suitable dispersant to improve the anode slurry’s compatibility with the carbon fabric and final uniform distribution of the anode materials. The anode with added dispersant exhibits a lower resistance, and the constructed cell presents a higher capacity than that without dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Several strategies have been developed to overcome these drawbacks, such as porous structure construction [9][10][11][12] , artificial solid-electrolyte-interface (SEI) layer formation [13][14][15][16] , and novel binder design [14,17,18] . Researchers also found that downsizing the Si particles to nanometers helps suppress particle pulverization, but the considerable surface area of nanosized Si leads to abundant side reactions, thus decreasing the Coulombic efficiency [19] . Carbon is widely used as a coating material on Si to improve its electrical conductivity and separate Si from the electrolyte [16,20,21] .…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been developed to overcome these drawbacks, such as porous structure construction [9][10][11][12] , artificial solid-electrolyte-interface (SEI) layer formation [13][14][15][16] , and novel binder design [14,17,18] . Researchers also found that downsizing the Si particles to nanometers helps suppress particle pulverization, but the considerable surface area of nanosized Si leads to abundant side reactions, thus decreasing the Coulombic efficiency [19] . Carbon is widely used as a coating material on Si to improve its electrical conductivity and separate Si from the electrolyte [16,20,21] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the primary uses in fuel cells and supercapacitors, CF has recently attracted interest as an electrode material for Li-ion batteries (LIBs). As a conductive host for electrode materials in LIBs, the 3D framework of CF not only accommodates the stress caused by volume change in the electrode active material during lithiation/delithiation but also enhances access to the electrolyte and maximizes the contact between the electrolyte and the electrode. , In addition, the CF consisting of strong and flexible fiber bundles can host the electrode materials without requiring an insulating organic binder . Simultaneously, the 3D conductive framework of CF enhances electron transport and hence eliminates the need for conductive agents, and the thick woven structure of CF permits a high areal mass loading of the electrode active material.…”
Section: Introductionmentioning
confidence: 99%
“…For example, coating the anode‐active FeS, 22 Fe 3 O 4 , 23,24 Fe 2 O 3 , 25 or TiNb 2 O 7 26 particles on the high‐surface‐area CF obtained free‐standing and flexible electrodes without the addition of organic binder for LIBs. The coating of MoS 2, 27 Si, 28 SnO 2 and 29 particles on CF facilitated the charge transfer and the accommodation of volume expansion of high‐energy electrodes upon cycling. Compositing the Li metal with CF mitigated the formation of Li dendrite on the anode and hence improved the cycling life span and even the safety issue of batteries 30 .…”
Section: Introductionmentioning
confidence: 99%